Projections of supply of and demand for agricultural products in Mexico to 1965, 1970 and 1975 - Mexico; Banco de México (1925- ) (Jerusalem : Published for the United States Dept. of Agriculture, Economic Research Service, by the Israel Program for Scientific Translations, 1966)
The purpose of this study is to review the prospects for supply of and demand for agricultural products in Mexico in 1965, 1970 and 1975, in order to quantify, given present conditions and trends, the foreseeable deficits or surpluses.
On spine: Mexico: agricultural supply and demand projections, 1965, 1970, 1975.
Includes bibliographical footnotes.
osc 30/01/2019
Loans
Keywords: Produce trade